The Effect of Financial Literacy, Social Support, and Financial Stress on Single-Mother Financial Well-being - Siti Sekar Ayu Fadillah; Irni Rahmayani Johan; Tin Herawati (UIN Sunan Gunung Djati, 2025)
The increasing rates of divorce and the growing number of female-headed households highlight important social dynamics that require serious attention. However, in 2023, only 60.31% of female heads of households were employed, creating economic challenges that affect fulfilling family needs. This situation reflects a gap between women's responsibilities and their access to economic resources. Women who assume dual roles must perform both instrumental and expressive functions, acting as breadwinners and caregivers who provide love and emotional Support to their children. These dual roles often increase the risk of stress, particularly in financial aspects. Single mothers tend to face various forms of vulnerability, including social, physical, emotional, and economic vulnerabilities, all of which can negatively impact overall family well-being. This quantitative research project uses an explanatory research design and a voluntary sampling technique. One hundred twenty-five single mothers participated as respondents, representing various age groups ranging from 25 to 57 years. The highest divorce status was widowhood (63.2%), followed by divorce due to separation (36.8%). Data were collected through a questionnaire tested for validity and reliability. The study results indicate that financial literacy has a positive and significant effect on financial stress, meaning that higher levels of financial literacy are associated with lower levels. Social Support also has a positive and significant effect on financial stress, indicating that Support from one's social environment can help reduce financial pressure. Furthermore, financial stress has a negative and significant effect on financial well-being, suggesting that increased financial stress leads to lower financial well-being.